2018
DOI: 10.2147/copd.s179734
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophil count as a prognostic biomarker in COPD

Abstract: BackgroundHigh blood eosinophil count is a predictive biomarker for response to inhaled corticosteroids in prevention of acute exacerbation of COPD, and low blood eosinophil count is associated with pneumonia risk in COPD patients taking inhaled corticosteroids. However, the prognostic role of blood eosinophil count remains underexplored. Therefore, we investigated the associated factors and mortality based on blood eosinophil count in COPD.MethodsPatients with COPD were recruited from 16 hospitals of the Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“… 29 , 30 Population-based studies included MESA (African American, non-Hispanic white, Hispanic, and Chinese participants), 31 , 32 Cardiovascular Health Study (CHS; African American and European ancestry participants), 33 the Rotterdam Study (all three cohorts), 34 and a study by Kangwon University. 35 For lung-function growth patterns, we did an analysis using individuals in the Childhood Asthma Management Program (CAMP). 18 CAMP was a randomised placebo-controlled trial of anti-inflammatory treatments in 1041 children with mild-to-moderate asthma (aged 5–12 years at enrolment), with 13 years of follow-up and low attrition (≤20%).…”
Section: Methodsmentioning
confidence: 99%
“… 29 , 30 Population-based studies included MESA (African American, non-Hispanic white, Hispanic, and Chinese participants), 31 , 32 Cardiovascular Health Study (CHS; African American and European ancestry participants), 33 the Rotterdam Study (all three cohorts), 34 and a study by Kangwon University. 35 For lung-function growth patterns, we did an analysis using individuals in the Childhood Asthma Management Program (CAMP). 18 CAMP was a randomised placebo-controlled trial of anti-inflammatory treatments in 1041 children with mild-to-moderate asthma (aged 5–12 years at enrolment), with 13 years of follow-up and low attrition (≤20%).…”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies also showed similar results. 5,[11][12][13] However, another study from France revealed there was no association of increased blood eosinophils and mortality of COPD patients regardless of the cutoff values. 14 There might be some reasons which can explain these discrepancies: most importantly, blood eosinophils naturally fluctuate over time and are affected by many factors.…”
Section: Discussionmentioning
confidence: 97%
“…The study subjects from our study and Li et al 13 were patients hospitalized for AECOPD, Salturk et al 5 study subjects were patients who were admitted to ICU with acute respiratory failure, while other studies' subjects were from stable COPD patients. 11,12,14 In addition, whether patients suffering with asthma were included or not may affect study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophils are key innate immune cells in host defence [3], and they have been found to be associated with mortality in patients with chronic obstructive pulmonary disease (COPD) [4,5] and asthma [6,7]. The blood eosinophil count (EOS) is considered a potential biomarker for the identi cation of COPD patients at risk and as a reference for the usage of inhaled corticosteroids, as recommended by the GOLD 2019 guidelines [8].…”
Section: Introductionmentioning
confidence: 99%